A Geolocation Visitors to the Polinema Library using QR Code and OTP Code on Internet of Things based Smart Locker - Dhelia Dhelia Balqis Zharifa Az-Zahra; Mohammad Abdullah Anshori; Putri Elfa Mas'udia (Jurnal Jaringan Telekomunikasi, 2023)
The library is one of the rooms or facilities used as a learning center. Data on library visitors with a locker at the Polinema library is in a different place, where the Polinema library locker are outside the library area which can be misused for storage of public goods. Visitors only enter the library area to ask for locker keys and leave items in the lockers, but visitors do not visit the library. To overcome this, a system was designed using a QR Code scan that can be used as a library visitor data system that can directly open the locker door using an OTP code, after getting the OTP code visitors can enter items and then lock them automatically. Application login testing can be done according to the system. Testing of open/closed locker markers and admins can access the locker if someone leaves the Library area. The coordinates of the GPS points for 4 visitors who came out of the Library area with a distance of 25,049m, 38,839m, 56,502m, and 64,904m were proven with a maximum distance of 20m. Comparison of the distance between Formula Haversine and Google Maps (distance between 2 points) obtained an accuracy rate of 0.236%.